2021
DOI: 10.1155/2021/7724455
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Response and Dissipated Energy Analysis of Sandstone under Freeze-Thaw Cycles

Abstract: Based on the sandstone from the slope of Baorixile open-pit mining area in Hulunbuir City, Inner Mongolia, the dynamic uniaxial compression test of sandstone with different freeze-thaw cycles has been carried out by Split Hopkinson Pressure Bar test (SHPB). The test results show that the crushing degree of sandstone becomes serious with the freeze-thaw cycle times and strain rate increases. The dynamic compressive strength increases with the raise of strain rate under the same freeze-thaw cycles, while it redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In Formula (12), α and m are the physical and mechanical parameters of the material, where α is the Weibull distribution parameter and m represents the non-uniformity of the distribution. Formulas (11) and (12) can produce…”
Section: Theoretical Analysis Of Sandstone Damage Characteristics Aft...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Formula (12), α and m are the physical and mechanical parameters of the material, where α is the Weibull distribution parameter and m represents the non-uniformity of the distribution. Formulas (11) and (12) can produce…”
Section: Theoretical Analysis Of Sandstone Damage Characteristics Aft...mentioning
confidence: 99%
“…The effects of freeze-thaw cycles and confining pressure on the creep properties, long-term strength, and creep failure mode of the rock were analyzed. Man et al [12] used sandstone from the slope of the Baorixile open-pit mining area in Hulunbuir City, Inner Mongolia, to perform split Hopkinson pressure bar tests after various freeze-thaw cycles. The test results showed that the extent of sandstone crushing increases with the freeze-thaw cycle time and strain rate.…”
Section: Introductionmentioning
confidence: 99%